2020
DOI: 10.1177/1455072520904651
|View full text |Cite
|
Sign up to set email alerts
|

The gendered relationship with drunkenness among different generations in Mediterranean and Nordic countries

Abstract: The study adopts a qualitative comparative approach to better understand how different dimensions affect social norms regulating alcohol consumption. Female and male attitudes towards drunkenness were analysed on the basis of data from 27 focus groups involving a total of 166 participants from Italy, Finland and Sweden, grouped by age cohort (17–20 and 50–65 years) and educational level. Results suggest that gendered drinking norms may be affected more by the drinking culture than by the degree of gender equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
(81 reference statements)
0
7
0
1
Order By: Relevance
“…On the other hand, in a more recent study, we showed that the all‐cause alcohol‐attributed disease burden was particularly high among Danes of both genders and Finnish males, and that gender differences were larger in Finland than in Denmark, Sweden or Norway [24]. Since males and females in the same country share the policy context, this implies that other factors are involved, such as socio‐cultural differences related to consumption [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a more recent study, we showed that the all‐cause alcohol‐attributed disease burden was particularly high among Danes of both genders and Finnish males, and that gender differences were larger in Finland than in Denmark, Sweden or Norway [24]. Since males and females in the same country share the policy context, this implies that other factors are involved, such as socio‐cultural differences related to consumption [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…A multigenerational transmission of psychiatric disorders was seen only for grandsons. One potential explanation could be that our operationalization of psychiatric disorders captures primarily substance-related disorders, and men are more likely to be affected by these disorders than women ( Rolando et al, 2020 ). However, further investigations that include many other factors (e.g., intra- and extra-familial influences such as parental separation, and relationships with peers ( Evans et al, 2013 ; Jobe-Shields et al, 2015 )) are needed to provide a better understanding on the mechanisms underlying this gender difference in the multigenerational transmission of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…En pocas palabras, las culturas húmedas, típicas de los países productores de vino, se han caracterizado tradicionalmente por una proporción muy elevada de bebedores y un consumo frecuente y excesivo, pero con pocos problemas sociales relacionados con la bebida, ya que los principales valores de uso del alcohol eran la socialización y la convivencia o como producto alimenticio, mientras que la intoxicación estaba estigmatizada. Por el contrario, las culturas secas, como las características de los países del Norte y de habla inglesa, suelen describirse como centradas en las bebidas espirituosas, con una menor proporción de bebedores y menos consumo excesivo, pero con mayores índices de consumo orientado a la intoxicación, acompañados de problemas sociales relacionados con el alcohol más frecuentes, como la violencia (Rolando et al, 2020).…”
Section: Jóvenes En Las Culturas De La Intoxicaciónunclassified